Conservation of migratory waterbirds and their wetland habitats in the east Asian-Australasian flyway : (The Preparatory Committee of the Kushiro International Wetland center, 1994)
These presentations were followed by a plenary discussion of operational issues, including the founding and maintaining of an international site network, applicability of Ramsar convention criteria to site selection and the development of a Shorebird action plan,...